About inadequacy of transformer equivalent circuits to its electromagnetic processes - Pridubkov, P. Y.; Khomenko, I. V. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2012)
Inadequacy of available equivalent circuits of a linear transformer to its electromagnetic processes is shown. Dependences of vector potential components on the transformer winding current density vectors distribution are analyzed. Formulas for stray flux through spatial components of four-dimensional potentials are derived.